(untitled) (Avocetta, 2024)
Mites of the genus Laminosioptes have been reported in domestic Galliformes birds and pigeons in some countries. They specifically infest the subcutaneous tissue of the host generating granulomatous lesions. In the current study, we reported the presence of Laminosioptes cysticola in the pectoral muscle of a specimen of Great Egret, Ardea alba egretta, found in the peri-urban area of Belém, Pará, Brazil. We discuss the role of this individual as vector of mites between domestic and wild birds and we recommend ornithologists and veterinaries to carry out careful observations of live and dead birds because small parasites such as the mites L. cysticola can easily remain undetected.